Mono-(2-ethylhexyl) phthalate Promotes Dengue Virus Infection by Decreasing IL-23-Mediated Antiviral Responses - Lin, Chun-Yu; Huang, Chung-Hao; Wang, Wen-Hung; Tenhunen, Jyrki; Hung, Ling-Chien; Lin, Chi-Chou; Chen, Yu-Cheng; Chen, Yen-Hsu; Liao, Wei-Ting (Frontiers in Immunology, 2021)
Exposure to environmental hormones such as di(2-ethylhexyl) phthalate (DEHP) has become a critical human health issue globally. This study aimed to investigate the correlations between DEHP/mono-(2-ethylhexyl) phthalate (MEHP) levels and macrophage-associated immune responses and clinical manifestations in dengue virus (DV)-infected patients. Among 89 DV-infected patients, those with DV infection-related gastrointestinal (GI) bleeding (n = 13, 15% of patients) had significantly higher DEHP exposure than those without GI bleeding (n = 76, 85% of patients), which were 114.2 ng/ml versus 52.5 ng/ml ΣDEHP in urine; p = 0.023). In an in vitro study using cultured human monocyte-derived macrophages (MDMs) to investigate the effects of MEHP, treatment increased IL-1β and TNF- release but decreased IL-23 release, with negative correlations observed between urine ΣDEHP and serum IL-23 levels in patients. MEHP-treated MDMs had lower anti-viral Th17 response induction-activity in mixed T-cell response tests. The in vitro data showed that MEHP increased DV viral load and decreased IL-23 release dose-dependently, and adding IL-23 to MEHP-exposed MDMs significantly reduced the DV viral load. MEHP also suppressed IL-23 expression via the peroxisome proliferator-activated receptor-gamma (PPAR-γ) pathway. Further, the PPAR-γ antagonist GW9662 significantly reversed MEHP-induced IL-23 suppression and reduced the DV viral load. These study findings help to explain the associations between high MEHP levels and the high global burden of dengue disease.